2014
DOI: 10.1038/ncomms5242
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 inhibition yields functional insulin-producing cells in human gut organoid cultures

Abstract: Generation of surrogate sources of insulin-producing β-cells remains a goal of diabetes therapy. While most efforts have been directed at differentiating embryonic or induced pluripotent stem (iPS) cells into β-like-cells through endodermal progenitors, we have shown that gut endocrine progenitor cells of mice can be differentiated into glucose-responsive, insulin-producing cells by ablation of transcription factor Foxo1. Here we show that FOXO1 is present in human gut endocrine progenitor and serotonin-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
84
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 33 publications
15
84
1
Order By: Relevance
“…Similarly, ablation of the transcription factor FOXO1 in endocrine progenitors of the intestine results in the generation of insulin-expressing cells that are able to reverse hyperglycemia in mice (36). This finding has been reproduced in human gut organoids (23), suggesting that FOXO1 inhibition in gut organoids could offer a source of insulin-producing cells to treat human diabetes. As human gastrointestinal tissue is readily accessible by noninvasive techniques, ex vivo reprogramming of gastrointestinal cells could be a source of autologous β cells for implantation in patients with diabetes.…”
Section: Introductionsupporting
confidence: 51%
“…Similarly, ablation of the transcription factor FOXO1 in endocrine progenitors of the intestine results in the generation of insulin-expressing cells that are able to reverse hyperglycemia in mice (36). This finding has been reproduced in human gut organoids (23), suggesting that FOXO1 inhibition in gut organoids could offer a source of insulin-producing cells to treat human diabetes. As human gastrointestinal tissue is readily accessible by noninvasive techniques, ex vivo reprogramming of gastrointestinal cells could be a source of autologous β cells for implantation in patients with diabetes.…”
Section: Introductionsupporting
confidence: 51%
“…FoxO1 deletion also leads to formation of insulin + cells in the intestine, suggesting a therapeutic path toward inducing insulin + cells in situ (Bouchi et al, 2014; Talchai et al, 2012a). Our approach offers several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Development of gut enteroendocrine and pancreatic endocrine cells also depends on common critical factors, such as Ngn3 (also known as Neurog3 ) (Gu et al, 2002; Jenny et al, 2002; Lee et al, 2002). Recent studies showed that intestinal cells could be converted into insulin + cells with either endocrine-specific deletion of FoxO1 or ubiquitous expression of NPM reprogramming factors ( Ngn3 , Pdx1 , and Mafa ) (Bouchi et al, 2014; Chen et al, 2014; Talchai et al, 2012a). Although these studies revealed the feasibility of deriving β-like cells from the intestine, critical barriers remain in developing these approaches into future regenerative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications to established protocols are likely to uncover new conditions required for specific aspects of division and differentiation of these preparations and reveal new translational applications. A recent example is the demonstration that inhibition of FOXO1 in human gut organoid cultures yields functional insulin-producing cells (60). Detailed documentation and comparisons will be necessary to properly define the genetic, biochemical, and physiologic aspects of the resulting enteroids and organoids.…”
Section: Future Needsmentioning
confidence: 99%